Perencanaan dan Perancangan Alun-alun Kabupaten Bekasi Sebagai Public Space Dengan Pendekatan Arsitektur Kontemporer - Hendah Habibah; Ahmad Aguswin; Windi Windi (LPPM Universitas Pahlawan Tuanku Tambusai, 2022)
The square is a public open space that can accommodate various community activities. Bekasi Regency Square was established with the aim of being able to meet the needs of green open space in the city area. and can be an alternative entertainment to unwind after undergoing routines and provide facilities for socializing, chatting and discussing for the people of Bekasi Regency, as social beings, society also needs open channels to interact and socialize with the community or other communities. in addition to increasing public open space in Bekasi Regency, especially in Cikarang where green open spaces or squares must be owned by an area. The location of the Alun-alun is in Bekasi Regency, precisely in North Cikarang District which is the location of Development I. In the development of green open space, the Square requires an attractive arrangement and appearance to increase the beauty and comfort of the city, in order to attract tourists. This design uses the concept of contemporary architecture which will be applied to the design of the existing building in the square. The application of contemporary principles is realized by applying a design that looks solid, and dynamic. With the Bekasi Regency square, the provision of green open spaces can be achieved